Group Counseling Self-Management Techniques in Reducing Nomophobia Through Self-Control - Hendar, Kus; Majdi, M. Zuhdi Zainul (COUNS-EDU: The International Journal of Counseling and Education, 2023)
Information technology is developing rapidly, especially for smartphone users. Smartphones have become a communication and information tool in everyday life. The activity of using smartphones with excessive intensity can cause various impacts on users, such as nomophobia. Someone who is unable to exercise self-control in using a smartphone or has low self-control will be susceptible to addiction. The research aims to determine the effectiveness of group counseling on self-management techniques to reduce nomophobia by increasing self-control. This research uses a pretest and posttest design. The subjects of this research were 10 people. The sampling used was purposive sampling. Data was collected using self-control and nomophobia questionnaires. Data analysis used mediation analysis with a bootstrap bias-corrected method with a confidential interval of 95% assisted by micro-process software (N=5000). The research results show that there is an effect of group counseling on effective self-management techniques in reducing nomophobia by increasing self-control.